The dawn of the bronze age : the pattern of settlement in the lower Jordan valley and the desert fringes of Samaria during the late chalcolithic period and early bronze age i - Bar, Shay. (Culture and History of the Ancient Near East, 2014)
In The Dawn of the Bronze Age Shay Bar presents a detailed account of the pattern of settlement during the Chalcolithic and Early Bronze Age I periods (mid-Fifth to late Fourth Millennia BCE), in one of the least explored areas of the southern Levant - the lower Jordan valley and the desert fringes of the Samaria mountains. More than 120 surveyed sites and five excavation reports form an essential database for every scholar interested in the archaeology of the Near East in these periods. "Bar has accomplished an impressive task and has provided valuable new information on this important region that forms the transition between the central hill country and the eastern side of the Jordan River." Eva Kaptijn, Royal Belgian Institute of Natural Sciences, Bibliotheca Orientalis LXXIV n° 1-2 (2017)